Experimental evaluation of solar multistage direct contact membrane distillation system for water desalination. (June 2022) - Khalifa, Atia E.; Abdalmonem, Ahmed; Alawad, Suhaib M.; Antar, Mohamed A.
Abstract: The performance of a solar-heated multistage direct contact membrane distillation system was experimentally evaluated for sustainable water production. Parallel and series connections of three DCMD stages for the feed and permeate streams were tested and compared. A mathematical model for a double glass evacuated tube solar collector was developed to predict the temperature variation of the stagnant feed water solar tank during heating. Results demonstrate the sustainability of water production using the integrated solar DCMD desalination system. Parallel connection of system stages is more productive compared to series connection. The system flux is decreasing over the day hours following the decreasing feed water temperature due to higher energy consumed by the DCMD desalination process compared to the solar energy received by the single solar collector. However, the system showed a very good level of water production sustainability over the day hours. The average fluxes from 9 AM to 6 PM are 51.6 kg/m 2 .h for the parallel multistage system and 22.1 kg/m 2 .h for the series multistage system, corresponding to an average solar tank (feed water) temperature of 66 °C. The parallel three-stage solar MD system produced 9 L of fresh water, with specific thermal energy consumption of about 1770 kWh/m 3 .